Curriculum Mapping in a Social Work Program With the 2015 Educational Policy and Accreditation Standards. (2nd January 2019) - Cheung, Monit; Zhou, Shu; Narendorf, Sarah C.; Mauldin, Rebecca L.
ABSTRACT: In a curriculum mapping project, the mapping process of an MSW program is documented and linked with the Council on Social Works Education's 2015 Educational Policy and Accreditation Standards competencies. It starts with the background of creating a mapping process for sequencing and integrating a series of assessment tasks with mapping exercises. An example focusing on this program's clinical specialization is provided. Curriculum mapping is defined as a step-by-step process of visualizing and evaluating teaching content for curriculum studies, from generalist to specialization. This process explains how to map and improve social work curricula with component analyses and provides suggestions for planning future mapping visualization exercises prior to reaffirmation studies.